Highly Sensitive Square Wave Voltammetric Determination of Sunset Yellow at a Functionalized‐MWCNTs/poly(Alizarin Red‐S) Composite Modified Electrode. Issue 10 (14th April 2022) - Güneş, Mehmet; Karakaya, Serkan; Dilgin, Yusuf
Abstract: This work presents an effective and highly sensitive electrochemical detection of Sunset Yellow (SSY) at poly(Alizarin Red‐S) and functionalized multi‐walled carbon nanotubes composite modified glassy carbon electrode ( f ‐MWCNTs/poly(ALR‐S)/GCE). The electrochemical response of the f ‐MWCNTs/poly(ALR‐S)/GCE towards SSY was examined by cyclic voltammetry (CV) and square wave voltammetry (SWV). Both recorded cyclic voltammograms (CVs) and square wave voltammograms (SWVs) showed that the oxidation/reduction peaks of SSY at f‐ MWCNTs/poly(ALR‐S)/GCE were found to be much higher than the bare GCE, f ‐MWCNTs/GCE, and poly(ALR‐S)/GCE. Calibration curves obtained from the SWVs indicated that the f ‐MWCNTs/poly(ALR‐S)/GCE offers a linear response in the range of 0.50 to 256 μM with a low detection limit (LOD) of 0.16 μM and the sensitivity was found to be 9686 μA mM −1  cm −2 . The f ‐MWCNTs/poly(ALR‐S)/GCE provides excellent performance for the detection of SSY in daily life samples with high accuracy and precision. Abstract :